2006
DOI: 10.1111/j.1440-1681.2006.04331.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparity of Streptozotocin‐induced Intrinsic Contractile Dysfunction in Murine Ventricular Myocytes: Role of Chronic Activation of Akt

Abstract: 1. Clinical, epidemiological and experimental evidence suggests a 'female advantage' in the progression of cardiovascular diseases, including diabetic cardiomyopathy. It is speculated that this 'gender bias' may be due to gender-related differences in sex hormones and intrinsic myocardial contractile properties. 2. The present study was designed to examine the impact of diabetes and gender on cardiac contractile function and activation of the cardiac survival signalling molecule Akt. Short-term (2 weeks) diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Our observation that catalase rescues diabetes-induced loss of pAkt is also consistent with our earlier data that the antioxidant metallothionein restores the loss of insulin-stimulated Akt phosphorylation (Ser473) in insulin resistance (Fang et al, 2005). It should be mentioned that enhanced Akt phosphorylation (Ser473) was also observed in hearts from the identical STZ-induced diabetic model in our lab (Ceylan-Isik et al, 2006a). Such disparity in diabetes-induced basal Akt phosphorylation may indicate a potential transition from a compensated (elevated Akt phosphorylation) to a decompensated (reduced Akt phosphorylation) in diabetic hearts.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation that catalase rescues diabetes-induced loss of pAkt is also consistent with our earlier data that the antioxidant metallothionein restores the loss of insulin-stimulated Akt phosphorylation (Ser473) in insulin resistance (Fang et al, 2005). It should be mentioned that enhanced Akt phosphorylation (Ser473) was also observed in hearts from the identical STZ-induced diabetic model in our lab (Ceylan-Isik et al, 2006a). Such disparity in diabetes-induced basal Akt phosphorylation may indicate a potential transition from a compensated (elevated Akt phosphorylation) to a decompensated (reduced Akt phosphorylation) in diabetic hearts.…”
Section: Discussionsupporting
confidence: 92%
“…While our study demonstrated early onset of cardiomyopathy in female diabetics, Ceylan-Isik et al reported that cardiomyocytes isolated from the female diabetic hearts were better protected than the cardiomyocytes from male diabetic hearts [36]. Similarly, cardiomyocytes isolated from young female diabetic mice by Zhang et al exhibited normal contractile function [37].…”
Section: Discussionsupporting
confidence: 50%
“…Insulin-deficient diabetes was induced in C57BL/6J mice (8 weeks male) by a single i.p. injection of streptozotocin (STZ; Sigma, St. Louis, MO; 2.5 mg per body-weight (BW(g)), which was dissolved in 0.1 M sodium citrate buffer (pH 4.5) just before injection, as described previously [13]. Age-matched normal control mice received saline alone.…”
Section: Animal Modelsmentioning
confidence: 99%